Frequently asked questions about emergency lifesaving techniques - Roza, Greg. (New York : Rosen Pub., 2010)
Offers teens an overview of lifesaving techniques, explaining airway management and CPR and providing information on treating wounds, bleeding, broken bones, poisoning, burns, and heat and cold emergencies.
What are the basics techniques of emergency lifesaving? -- What are airway management and CPR? -- How do I treat wounds, bleeding, and broken bones? -- How do I treat poisoning? -- How do I treat burns? -- How do I treat heat and cold emergencies?.
Includes bibliographical references (p. 61) and index.
6.8
Young Adult.
Young Adult
Keywords: First aid in illness and injury -- Juvenile literature; Lifesaving -- Juvenile literature; First aid; Lifesaving; First aid; Lifesaving